Vegetable oil-based epoxy resins and their composites with bio-based hardener: a short review - Rohani, Mustapha; Abdul Razak, Rahmat; Rohah, Abdul Majid; Siti Noor Hidayah, Mustapha (Taylor & Francis, 2019)
Vegetable oil (VO) is the latest alternative found to be one of the ideal candidates for production of bio-based polymeric units. There are two main methods for producing bio-based epoxy resins and composites: the direct synthesis of VO and the blends of epoxy with VO incorporated with natural or synthetic fibers. However, it is more challenging to produce a fully green bio-based epoxy composite, as they have relatively low strength that limits their applications. Thus, this article is designed to review the present research advances on VO-based epoxy resins and their composites with bio-based hardener incorporated with fibers or fillers.